Python for MATLAB Development - Extend MATLAB with 300,000+ Modules from the Python Package Index - Danial, Albert (Apress, an imprint of Springer Nature, 2022)
This book shows you how to enhance MATLAB with Python solutions to a vast array of computational problems in science, engineering, optimization, statistics, finance, and simulation. It is three books in one: A thorough Python tutorial that leverages your existing MATLAB knowledge with a comprehensive collection of MATLAB/Python equivalent expressions. A reference guide to setting up and managing a Python environment that integrates cleanly with MATLAB. A collection of recipes that demonstrate Python solutions invoked directly from MATLAB. This book shows how to call Python functions to enhance MATLAB's capabilities. Specifically, you'll see how Python helps MATLAB: Run faster with numba; Distribute work to a compute cluster with dask; Find symbolic solutions to integrals, derivatives, and series summations with SymPy; Overlay data on maps with Cartopy; Solve mixed-integer linear programming problems with PuLP; Interact with Redis via pyredis, PostgreSQL via psycopg2, and MongoDB via pymongo; Read and write file formats that are not natively understood by MATLAB, such as SQLite, YAML, and ini.